Crossing the rubicon - "Mohan, C Raja" (New Delhi, 2003)
India$1 (Bs nuclear tests in May 1998 had reverberations that went far beyond the Thar desert. Jettisoned, as a result, were some key tenets of its foreign policy, in particular the traditional emphasis on idealism. As pragmatism took root in New Delhi, Indiarenewed its global engagement with a rare sense of purpose and self - confidence and transformed its external relations in Crossing the Rubicon. s
Keywords: Foreign relations - India